THE PLACE OF ECONOMIC AND LEGAL RELATIONS IN THE SYSTEM OF LEGAL RELATIONS OF UKRAINE (THEORETICAL AND LEGAL APPROACH) - Milimko, Larysa; Yakivchuk, Jeanne (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: based on the analysis of current legislation, the views of scientists to determine the place of economic relations in the system of legal relations of Ukraine, to characterize them and make suggestions for improving these relations under modern conditions. Methods: the study was conducted using such methods as historical, analysis, synthesis, extrapolation. Results: in the article the author gives the characteristic of economic legal relations, their place in the system of legal relations of Ukraine is defined. Emphasis is placed on the fact that economic relations are regulated by the rules of commercial law, which at the present stage is a complex branch of law, the rules of which regulate the relations of the economic sphere in the public and private spheres. Economic relations are closely related to administrative and civil relations, but are delineated by the boundaries of economic activity and its organization, the specific subject composition and focus on the public interest, along with private. Despite the separation of the Civil Code of Ukraine (Article 4) of relations in the field of management from other relations, in practice there are a number of problems in this regard and on which attempts are being made to resolve in court. Thus, this problem requires further research and development. Discussion: problems in determining the place of economic and legal relations in the legal system of Ukraine. Disputes between scholars and practitioners over the boundaries of economic relations have been going on for a long time, and the question of the expediency of the Commercial Code was considered before its adoption. Currently, this problem has been exacerbated, in particular by internal disputes, as well as due to the adaptation of domestic legislation to the legislation of the European Union in connection with Ukraine’s association agreements with the EU and gradual modernization of Ukrainian legislation and efforts to bring it into line with European standards. First of all, scholars and practitioners state the fact of the difficulty of distinguishing economic relations from legal relations of other branches of law, as well as the inconsistency of the Commercial Code of Ukraine with current needs and other legal acts, which entails certain problems in implementing economic legislation in economic relations.